2021
DOI: 10.1002/pen.25807
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and modeling of modified styrene–acrylonitrile/carboxylated acrylonitrile butadiene rubber nanocomposites filled with graphene and graphene oxide: Interfacial interaction and nonlinear elastoplastic behavior

Abstract: Nonlinear elastoplastic behavior of the nanocomposites based on the styreneacrylonitrile/carboxylated acrylonitrile butadiene rubber (SAN/XNBR) blend was investigated using experimental and theoretical analysis. Graphene, graphene oxide nanoparticles, and glycidyl methacrylate-grafted-XNBR (XNBR-g-GMA) as a compatibilizer were incorporated in the SAN/XNBR blends. In this regard, the focus of this study is on modeling of the stress-strain behavior of these nanocomposites, considering the effect of the interfaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…25 Thus, it has been employed in diverse uses such as appliances, consumer goods, packaging, electrical products, medical tools, and automotives. [26][27][28] Nanofibers have been incorporated into polymer bulks as reinforcement agents, producing nanofiber-reinforced composite materials with improved mechanical properties. [29][30][31][32][33][34][35] Both of aerospace and automotive industrial sectors are two examples that have benefited from the widespread uses of nanofiberreinforced plastics.…”
Section: Introductionmentioning
confidence: 99%
“…25 Thus, it has been employed in diverse uses such as appliances, consumer goods, packaging, electrical products, medical tools, and automotives. [26][27][28] Nanofibers have been incorporated into polymer bulks as reinforcement agents, producing nanofiber-reinforced composite materials with improved mechanical properties. [29][30][31][32][33][34][35] Both of aerospace and automotive industrial sectors are two examples that have benefited from the widespread uses of nanofiberreinforced plastics.…”
Section: Introductionmentioning
confidence: 99%
“…So far, several studies have been conducted on the use of fillers such as nanoscale graphene to improve the properties of polyamides [37]. This improvement includes strengthening the mechanical properties, reducing the permeability and better flame retardancy [38][39][40][41][42]. Studies have shown that nanoparticles with high aspect ratio have complex effects such as lamination.…”
Section: Introductionmentioning
confidence: 99%
“…GO is employed to prepare reduced GO and enhance the physical properties of polymeric composites. [19][20][21][22][23][24][25][26] The thermal and mechanical characteristics of a PVA/starch matrix have been improved using GO because its chemical structure with OH and COOH groups can regulate the film's shape and aggregation by a chemical combination. 13,27 Actacid orange RL (AO-RL) dye was removed using different polymeric-GO nanocomposites, such as GO/polypyrrole, GO/polyaniline, and GO/polystyrene.…”
Section: Introductionmentioning
confidence: 99%
“…Graphene oxide (GO) is one of the graphene derivatives, a two‐dimensional (2D) carbonaceous flake containing various active functional groups, such as carboxyl and hydroxyl. GO is employed to prepare reduced GO and enhance the physical properties of polymeric composites 19–26 . The thermal and mechanical characteristics of a PVA/starch matrix have been improved using GO because its chemical structure with OH and COOH groups can regulate the film's shape and aggregation by a chemical combination 13,27 .…”
Section: Introductionmentioning
confidence: 99%